Unwanted emission OTA test environment analysis of 5G basestation - Jian GONG; Nan NAN (Dianxin kexue)
Based on the strict unwanted spurious emission OTA requirements of China local regulation for 5G 2 600 MHz Base Station,the path loss of the different chambers including far field,CATR (compact antenna test range),near field,DBFC (dynamic beam forming compact range chamber) and other key factors were presented and analyzed according to the measured data.The compared results in different test environment were also shown and the suggestion for passing the test were given.